Supported two- and three-dimensional vanadium oxide species on the surface of β-SiC. Issue 17 (1st August 2017) - Carrero, Carlos A.; Burt, Samuel P.; Huang, Fangying; Venegas, Juan M.; Love, Alyssa M.; Mueller, Philipp; Zhu, Hao; Grant, Joseph T.; Mathison, Ricardo; Hanraham, Michael P.; Rossini, Aaron; Ball, Madelyn; et al.
Abstract : Dispersing two-dimensional VO x species on β-SiC offers a new approach to scale up propane ODH. Abstract : A series of supported two- and three-dimensional vanadium oxide surface species on β-SiC with various V coverages are prepared via incipient wetness impregnation and characterized by a variety of ex and in situ techniques. The oxidative dehydrogenation of propane (ODHP) is also used as a probe reaction to complementarily distinguish between two- and three-dimensional VO x surface species. Herein, we show that treating pristine β-SiC with oxygen transforms the existing amorphous SiO x C y surface layer into a more SiO2 -type layer, though with a negligible formation of Si–OH sites, which initially were expected to be the anchor sites for VO x species. In its place, the C–OH functional groups identified by X-ray photoelectron spectroscopy (XPS) act as anchor sites for the VO x species during the impregnation process, and are consumed as a function of V coverage. Our experimental observations all corroborate the formation of two- and three-dimensional VO x species on the surface of β-SiC.